High Thrill and Adventure Seeking is Associated with Reduced Interoceptive Sensitivity: Evidence for An Altered Sex–Specific Homeostatic Processing in High–Sensation Seekers. Issue 5 (September 2014) - Kruschwitz, J. D.; Lueken, U.; Wold, A.; Walter, H.; Paulus, M. P.
The personality trait of sensation seeking (SS) has been traditionally linked to the construct of exteroception, that is, sensing of the outside world. Little is known about the relationship between SS and interoception, that is, sensing originating in the body. Interoceptive sensations have strong affective and motivational components that may influence behaviours such as risk taking in SS. This investigation examined whether interoceptive differences contribute to different behavioural characteristics in SS. Using an inspiratory resistive load breathing task, the response to an aversive interoceptive stimulus as a basic homeostatic process was studied in 112 subjects (n = 74 women and 38 men). A linear mixed–model approach was used to examine the influence of thrill and adventure seeking (TAS) on the interoceptive response across three levels of breathing resistances (10, 20, and 40 cm H2 O/L/second). High–TAS relative to low–TAS individuals were less responsive in evaluating intensities of perceived choking with increasing inspiratory resistive loads. This effect was driven by male, but not female, high–TAS individuals and was particularly associated with reduced interoceptive sensitivity in men. The conceptualization of SS as primarily driven by exteroceptive stimuli can be expanded to a view of an altered homeostasis in SS, specifically in men. Copyright © 2013 European Association of Personality Psychology